Habitat occupancy of the threatened Diademed Plover (Phegornis mitchellii) is not affected by llama grazing or peatland size, but declines with peatland humidity - Pietrek, Alejandro G. (2024)
Fil: Pietrek, Alejandro G. University of California Santa Cruz. Ecology and Evolutionary Biology Department. Santa Cruz, CA; United States of America.